Survey of Molecular Mechanisms of Hyperbaric Oxygen in Tissue Repair - Joerg Lindenmann (MDPI AG, 2021)
For more than six decades, hyperbaric oxygen (HBO) has been used for a variety of indications involving tissue repair. These indications comprise a wide range of diseases ranging from intoxications to ischemia-reperfusion injury, crush syndrome, central nervous injury, radiation-induced tissue damage, burn injury and chronic wounds. In a systematic review, the molecular mechanisms triggered by HBO described within the last two decades were compiled. They cover a wide range of pathways, including transcription, cell-to-cell contacts, structure, adhesion and transmigration, vascular signaling and response to oxidative stress, apoptosis, autophagy and cell death, as well as inflammatory processes. By analyzing 71 predominantly experimental publications, we established an overview of the current concepts regarding the molecular mechanisms underlying the effects of HBO. We considered both the abovementioned pathways and their role in various applications and indications.